Impact of the Pandemic on Damaging the Democratic Process in a Hybrid Regime in Georgia - Chedia, Beka (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2023)
In hybrid political system of Georgia, in condition of COVID-19, the population obeyed control and strict regulations. Concepts such as the Iron Curtain, curfew, etc., have returned to the country’s political vocabulary. How can these symbols of a totalitarian (Soviet) past fit into the process of democratization? What is the reaction of society, other political actors? Why and how pandemic damaged democracy in Georgia? Does this threaten to revise the concept of a democratic political system, which will be especially difficult for post-totalitarian society? This research paper examines case of Georgia: how political institutions, political elite, society, Media, the country’s legislative base was ready for new reality and what political consequences this crisis would have in the process of democratization and nation-building. Unfair political competition during the elections, the growth of populism, the partial abandonment of certain rights, the deepening of polarization, etc. – are these challenges related only to the pandemic or have they also threatened Georgian democracy in “normal” times?

W hybrydowym systemie politycznym Gruzji, w realiach pandemii COVID-19, ludność podlegała kontroli i surowym przepisom. Pojęcia takie jak żelazna kurtyna, godzina policyjna itp. powróciły do słownictwa politycznego. Jak te symbole totalitarnej (sowieckiej) przeszłości mogą wpasować się w proces demokratyzacji? Jaka jest reakcja społeczeństwa, innych aktorów politycznych? Dlaczego i jak pandemia wpłynęła destrukcyjnie na demokrację w Gruzji? Czy grozi to rewizją koncepcji demokratycznego systemu politycznego, co będzie szczególnie trudne dla społeczeństwa posttotalitarnego? W niniejszym artykule autor poddaje analizie Gruzję, a w szczególności: jak instytucje polityczne, elity polityczne, społeczeństwo, media, legislatura państwa były gotowe na nową rzeczywistość i jakie polityczne konsekwencje miałby ten kryzys w procesie demokratyzacji i budowania narodu. Nieuczciwa rywalizacja polityczna podczas wyborów, wzrost populizmu, częściowa rezygnacja z niektórych praw, pogłębianie się polaryzacji itp. – czy to wyzwania związane tylko z pandemią, czy też zagrażały gruzińskiej demokracji także w „normalnych” czasach?
Wpływ pandemii na trudności procesu demokratycznego w gruzińskim reżimie hybrydowym
Keywords: Georgia; hybrid regime; COVID-19; elections; crisis; populism; democratic standards; Gruzja; reżim hybrydowy; COVID-19; wybory; kryzys; populizm; standardy demokratyczne